Distribution of polymorphisms IL4 -590 C/T and IL4 RP2 in the human populations of Madeira, Azores, Portugal, Cape Verde and Guinea-Bissau - Berenguer, Anabela G. (2020)
The IL4 gene is located on chromosome 5q23.3-31.2. Polymorphisms within this cytokine gene, like the derivative allele T of IL4-590, have been reported as being associated to elevated IgE serum levels and asthma. In the present work, the allelic and genotypic frequency of the IL4-590 and IL4 RP2 polymorphisms was carried out in 599 individuals from Madeira, Azores, Portugal mainland, Cape Verde and Guinea-Bissau and in a sample of 101 asthmatics from Madeira population. In all populations the polymorphisms were in LD and presented a significant dissimilar allelic and genotypic distribution (p<0.05) except between mainland Portugal and Madeira when compared to Azores. Significant differences regarding both loci were found between Madeira population and the group of asthmatics. Genotype 183183TT frequency is higher for African populations while 253253CC prevails in Caucasian populations. The existence of a Hardy-Weinberg Disequilibrium in Guinea-Bissau population not observed in neutral markers leads to the hypothesis of natural selection occurring in these loci probably associated to a rapid population growth an hypothesis strengthened by neutral STRs D5S818 and CSF1PO gene diversity.